Case Report of Necrotizing Fasciitis Associated with Streptococcus pneumoniae - Lei Jiao; Zain Chagla; Reham Mohammedsaeed Kaki; Gabriela Gohla; Marek Smieja (Canadian Journal of Infectious Diseases and Medical Microbiology, 2016)
Necrotizing fasciitis, caused by Streptococcus pneumoniae, is an extremely rare and life-threatening bacterial soft tissue infection. We report a case of early necrotizing fasciitis associated with Streptococcus pneumoniae infection in a 26-year-old man who was immunocompromised with mixed connective tissue disease. The patient presented with acute, painful, erythematous, and edematous skin lesions of his right lower back, which rapidly progressed to the right knee. The patient underwent surgical exploration, and a diagnosis of necrotizing fasciitis was confirmed by pathological evidence of necrosis of the fascia and neutrophil infiltration in tissue biopsies. Cultures of fascial tissue biopsies and blood samples were positive for Streptococcus pneumoniae. To our knowledge, this is the first report of necrotizing fasciitis resulting from Streptococcus pneumoniae diagnosed at early phase; the patient recovered well without surgical debridement.